Analisis Customer Experience Terhadap Customer Satisfaction Konsumen Onevape Store - Marliana, Enna; Pertiwi, Friza; Dwi Nur Rizki, Ilham; Bimo Syahputro, Satrio (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
During the current era of globalization that continues to grow, there is a lot of fierce competition between existing companies. One of the impacts of globalization is the emergence of electronic nicotine conductors as electronic cigarettes or now known as vape. The purpose of this study is to analyze customer experience on customer satisfaction of onevape store consumers. The method used in this study is qualitative research using interviews and observations. The data obtained in this study uses primary data sourced from owners, employees and customers and uses secondary data sourced from interviews and observations as well as previous research. The results of the study show that the quality of service provided by Onevape Store which provides services to customers is not only limited to product sales but also with the nature of hospitality and does not hesitate to provide the knowledge and knowledge it has to its customers.